2007
DOI: 10.1016/j.jaci.2007.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of omalizumab in adults with severe asthma: Results from the Asthma Policy Model

Abstract: Background-Omalizumab (trade name Xolair) is approved by the US Food and Drug Administration for treatment of moderate-to-severe allergic asthma. Given the high acquisition cost of omalizumab, its role and cost-effectiveness in disease management require definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 43 publications
0
76
1
2
Order By: Relevance
“…In addition, despite the relatively high cost of omalizumab (€10 000-15 000 per year per patient [153]), this treatment remains cost-effective (by decreasing severe exacerbations) when applied to well-selected patients, with a price by quality-adjusted life-year (QALY) ranging from €26 000 to €38 000 [65,139,153,154], whereas other studies in less selected asthmatics [154,155] concluded that omalizumab was not cost-effective (from US $280 000-800 000 per QALY). This cost-effectiveness evaluation further highlights the importance of properly selecting patients for biotherapies (currently referred to as personalised medicine).…”
Section: Ige As a Therapeutic Target And A Biomarker In Asthmamentioning
confidence: 99%
“…In addition, despite the relatively high cost of omalizumab (€10 000-15 000 per year per patient [153]), this treatment remains cost-effective (by decreasing severe exacerbations) when applied to well-selected patients, with a price by quality-adjusted life-year (QALY) ranging from €26 000 to €38 000 [65,139,153,154], whereas other studies in less selected asthmatics [154,155] concluded that omalizumab was not cost-effective (from US $280 000-800 000 per QALY). This cost-effectiveness evaluation further highlights the importance of properly selecting patients for biotherapies (currently referred to as personalised medicine).…”
Section: Ige As a Therapeutic Target And A Biomarker In Asthmamentioning
confidence: 99%
“…Eight studies compared monotherapy vs monotherapy (38,41,42,45,46,51,56,58). Four studies compared add-on omalizumab vs usual care (39,47,57,60). There was one study over the time period that considered the costs of reliever therapies, but since no health outcome was reported this study was excluded (62).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Of these, one study of leukotriene modifiers concluded that they were dominated by non-LM use (42). Two studies concluded that the additional cost of omalizumab was not worth the observed benefits for most patients with severe asthma (47,60). In an analysis of two asthma care strategies compared to usual care Sullivan et al (28) reported ICERs without making an assumption of the willingnessto-pay.…”
Section: Quality Assessment Resultsmentioning
confidence: 99%
“…[35]. Еще в одной работе использование омализумаба в США было признано неце-лесообразным до тех пор, пока производитель не добьет-ся существенного снижения цены препарата [36]. В двух работах сделано заключение об экономической нецелесо-образности омализумаба в США [37] и в Италии [38].…”
Section: резюме основного результата исследованияunclassified